KELIMPAHAN PLANKTON DI PERAIRAN BANGKA-BELITUNG DAN LAUT CINA SELATAN, SUMATERA, MEI - JUNI 2002 - Hikmah, Hikmah (UI Scholars Hub, 2004)
Plankton Abundance in Bangka – Belitung and South China Sea Waters, May - June 2002. The observation of plankton condition in Bangka, Belitung and South Cina Sea was conducted during May – June 2002. The parameters observed were focused on the microplankton and macroplankton communities. Twenty seven points of observation were grouped into two locations based on the distance of the observation station. Plankton abundance varied with location groups from 2069 to 23392 cells/l and 1249 to 5448 individuals/m3 for microplankton and macroplankton, respectively. Microplanktonic community structure was dominated by the group of diatoms, such as Skeletonema, Chaetoceros, Rhizosolenia, and Thalassiothrix. The genus Ceratium, Dinophysis and Protoperidinium (the group of dinoflagellates) was found in relatively abundant, but still in normal condition. The structure of macroplankton was dominated by the group of copepods (50 – 89%) and larvacea (10- 30 %).